Hubungan Dukungan Keluarga dengan Menstrual Distress pada Remaja Putri di Klaten - Permatasari, Devi; Sina Putriningsih, Rahma; Sat Titi Hamranani, Sri; Elsera, Chori; Dhian, Arlina (Universitas Muhammadiyah Klaten, 2025)
Being a teenager is like being in the middle of a big transformation from being a kid to becoming a grown-up. Lots of stuff happens during this time, including hormonal, social, psychological, and behavioral adaptations to internal pressures (stressors). Family support is the most effective support system that can help alleviate psychological pressure. In this study, the instruments used were. Family support and MEDI-Q. the research population was selected using the spearman rank. Out of 70 respondents, 18 (25,7%) had strong family support, 50 (71,45) had moderate family support, and 2 (2,9%) had weak family support. Respondents with mild menstrual distress numbered 37 (52,9%), while 31 (44,3%) experienced moderate menstrual distress, and 2 (2,9%) had severe menstrual distress. When we looked at the spearman test results, we found that there was a strong connection between how much support a girl gets from her family and how much she struggles with her period. This means that having a supportive family can make a big difference in how hard it is for a girl to deal with her period Keyword: Family support, distress symptoms, menstrual distress